TECHNOLOGY INTEGRATION IN EARLY CHILDHOOD AND PRIMARY CLASSROOMS - Shirin Daniyarovna Iskanderova (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article explores the integration of technology in early childhood and primary education classrooms, highlighting its potential to enhance learning experiences and support diverse learner needs. It examines current trends, benefits, and challenges associated with the use of digital tools and interactive media in early education settings. Emphasis is placed on how technology can foster creativity, collaboration, and critical thinking among young learners while supporting individualized instruction. The article also discusses the role of educators in effectively implementing technology, ensuring age-appropriate use, and addressing equity issues. Findings suggest that thoughtful integration of technology, combined with pedagogical best practices, can significantly enrich early learning environments and prepare children for a digital future.